Bibliometric analysis of studies on the Flipped Classroom Model in biology teaching - Hüseyin Cihan Bozdağ; Suat Türkoğuz; İsa Gökler (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
The global acceleration of studies on the Flipped Classroom Model (FCM) has revealed the necessity of literature review analyzes that shed light on research activities by examining the research data as a whole.  Therefore, in this study, it is aimed to examine academic publications on the FCM studies applied in biology teaching in terms of bibliographic variables. For this aim, the bibliometric analysis method was preferred in the study, which was carried out with a case study approach for an in-depth examination. Within the scope of the study, 53 publications obtained from the Scopus database for the entire time period were examined. In order to analyze these publications as a whole, the Scopus database and the VOSviewer program was used. According to the results, it is determined that the most preferred keywords are flipped classroom, active learning, online learning, flipped learning and biology, the most commonly used terms in the title and abstract section are students, courses, classroom, study and flipped classroom, the most common types of publications are article and papers, the most active country in terms of the number of studies is the USA, and the publication language is generally English. This study will help researchers and educators identify trends and issues that can guide future work involving the FCM.